(untitled) (Minerva. Revista de Filología Clásica, 2023)
Reseña de Jeremiah Coogan, Eusebius the Evangelist: Rewriting the Fourfold Gospel in Late Antiquity, New York, Oxford University Press, 2023, 234 páginas, ISBN 9780197580042